2013
DOI: 10.1148/radiol.12120254
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Primary Colorectal Cancer Heterogeneity by Using Whole-Tumor Texture Analysis: Contrast-enhanced CT Texture as a Biomarker of 5-year Survival

Abstract: FRCR Purpose:To determine if computed tomographic (CT) texture features of primary colorectal cancer are related to 5-year overall survival rate. Materials and Methods:Institutional review board waiver was obtained for this retrospective analysis. Texture features of the entire primary tumor were assessed with contrast material-enhanced staging CT studies obtained in 57 patients as part of an ethically approved study and by using proprietary software. Entropy, uniformity, kurtosis, skewness, and standard devia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
277
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 385 publications
(314 citation statements)
references
References 21 publications
22
277
3
Order By: Relevance
“…CT texture analysis is an emerging technique that quantifies heterogeneity of a region of interest by analyzing the distribution and/or relationship of pixel or voxel gray levels in the image [17]. This technique has been most intensely studied in oncologic applications, and has shown association with pathologic features and clinical outcomes in a variety of tumor types [18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Some non-oncologic applications are being evaluated, with several groups using texture analysis to assess emphysema and fibrosis in the lung [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…CT texture analysis is an emerging technique that quantifies heterogeneity of a region of interest by analyzing the distribution and/or relationship of pixel or voxel gray levels in the image [17]. This technique has been most intensely studied in oncologic applications, and has shown association with pathologic features and clinical outcomes in a variety of tumor types [18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Some non-oncologic applications are being evaluated, with several groups using texture analysis to assess emphysema and fibrosis in the lung [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Its value lies in detecting subtle alterations in appearance of a tissue early in the pathological process, invisible to the naked eye. TA has proven of value in several radiological studies, including colorectal cancer prognosis, structural changes in myoclonic epilepsy and differentiation of types of gastric tumour [19][20][21][22]. It has also demonstrated utility in the musculoskeletal system, for instance in evaluating articular cartilage at the knee and bone structure at the femoral neck [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, contrast enhanced CT measuring tumour heterogeneity could emerge as a biomarker for prognosis. Study has found tumours demonstrating less heterogeneity were associated with poorer survival, supporting the use texture analysis to staging contrast-enhanced CT, and possibly serve as a prognostic biomarker in colorectal cancer [54].…”
Section: Imaging Biomarkersmentioning
confidence: 84%